The main idea of «Мәңгілік ел» is an important value to educate young generation (Journal of Philosophy Culture and Political Science, 2018)
This article examines the issues of human and national values in realization of Kazakhstan’s idea of «Мәңгілікел».It reveals the basic ideas of human values and their characteristics as a way of formation of the younger generation. Universal values unite different people, religions and times, plus give the goals of one common spiritual phenomenon. The new nation’s mentality and its social relations are interconnected with human and national values. Universal valuations of education are important tools for the national history and philosophy’s development and traditions. The basic goals of modern educational system are formation in philosophy structure and mentality of young generation. One of the main traditions in Kazakh culture is an establishment of cognitive and communicative links among people. The idea of Kazakh national independence and spirit is supported these days. It is rooted in citizens’ mind of the state and has great prospects for the future. The modern educational system can integrate human and national values into one universal valuation for the society strengthening confidence in the future. A creative idea of the Kazakh society defines the dignity and the free development of future generations, symbolizing the proud flag of Kazakhstan.Key words: human values, national values, national independence, traditions.